SITUATIONALLY FREE RULES OF SPEECH ETHICS - Likhachev Sergey Vladimirovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
According to the definition of a small academic dictionary of the Russian language, ethics is understood as “norms of behavior, human morality”. The ethics of speech communication consists of the rules of speech behavior, among which there are strictly defined by the situation of the beginning or end of communication: greeting or farewell formulas, but there are also rules that can be used in various situations. Despite the existence of these rules, the ethics of speech is often understood only as a set of ready-made phrases of polite communication - speech etiquette.